2019
DOI: 10.3390/catal9060527
|View full text |Cite
|
Sign up to set email alerts
|

WO3–V2O5 Active Oxides for NOx SCR by NH3: Preparation Methods, Catalysts’ Composition, and Deactivation Mechanism—A Review

Abstract: Researchers in the field of the selective catalytic reduction (SCR) of nitrogen oxides (NOx: NO, NO2, or N2O) by NH3 are still greatly challenging the optimization of low-temperature activity and selectivity, high-temperature stability, resistance to alkali metals and other poisoning agents, such as Hg, As, etc. The present study reviews the research progress, related to the latest 20 years, on WO3–V2O5-based catalysts that are expected to overcome the catalytic performances of the current SCR catalytic device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…It can be concluded that TGA profiles of all spent catalysts using in the reaction exhibited similar activity (not shown data). At temperature higher than 200 °C, it was found that the addition of tungsten into TiO2 catalysts promoted the coke formation due to the interaction between W and TiO2 support introducing the catalyst burning [21,22]. The amount of coke formation in spent catalysts were determined and reported in Table 3.…”
Section: Thermal Gravimetric Analysis (Tga)mentioning
confidence: 99%
“…It can be concluded that TGA profiles of all spent catalysts using in the reaction exhibited similar activity (not shown data). At temperature higher than 200 °C, it was found that the addition of tungsten into TiO2 catalysts promoted the coke formation due to the interaction between W and TiO2 support introducing the catalyst burning [21,22]. The amount of coke formation in spent catalysts were determined and reported in Table 3.…”
Section: Thermal Gravimetric Analysis (Tga)mentioning
confidence: 99%
“…SCR catalysts consisting of V 2 O 5 -WO 3 /TiO 2 generally have very high Ti, W and V content, so it can be an economic and environmental feasible option to recover and reuse them. Ti, W, and V remanufactured after recovery can be used as raw materials for new catalysts or as raw materials in other industries 4,12,13 . Accordingly, technology development studies are actively being conducted to recover and remanufacture raw materials from waste catalysts 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction with NH 3 (NH 3 -SCR) is the most popular technology to eliminate the emission of nitrogen oxides (NO x ) from industrial flue gas, in which the DeNO x catalysts play the key role due to their high denitration (DeNO x ) efficiency [1][2][3][4]. As the most common commercial catalyst, the honeycomb DeNO x catalysts are largely produced though an extrusion process using industrial titanium dioxide or titanium-tungsten as Ti sources [5][6][7]. To reduce the production cost, our previous study invented a simplified technology process to produce honeycomb catalyst using filter cake as the Ti source derived from hydrothermal treatment of the metatitanic acid precursor [8].…”
Section: Introductionmentioning
confidence: 99%